Pilot scale anaerobic digestion of food waste - Lim, Wei Jie (2017)
Anaerobic digestion is a green and cost effective in handling a high volume of food waste in Malaysia. The main goal of this study is to assess the effect of substrate compositions on compost quality and profiling pattern of anaerobic digester. This study of food waste digestion using pilot scale Cowtech anaerobic digester was to optimize the proportion of food waste, dry leaf and cow manure as the substrates. The feeding of substrate and discharging of food waste compost were at rate of 40 kg/day at 40% capacity of the pilot scale anaerobic digester. The simplex centroid mixture design was applied to obtain optimum mixture proportion with three responses, including C/N ratio, pH and electrical conductivity. The optimization experiments were studied with the goal settings of compost qualities including C/N ratio was 21, pH at 8 and electrical conductivity at 1 dS/m for a single digestion of pure food waste and co-digestions of food waste with dry leaf or cow manure. Based on goal settings above, the optimum pure food waste proportion of 51.3% of vegetable waste, 30.3% of fruit waste and 18.4% of meat waste for pure food waste study. When dry leaf was included in the mixture proportion optimization, the optimum mixture was 1.2% of vegetable waste, 4.9% of fruit waste, 7.1% of meat waste and 86.8% of dry leaf. When cow manure was included in the mixture proportion optimization, the optimum mixture was 23.2 % of vegetable waste, 34.3% of fruit waste, 36.5% of meat waste and 6% of cow manure. The nutrient content from pure food waste compost was compared with those with co-digested of dry leaf or cow manure. The nutrient content of pure food waste was 0.067% in nitrogen content, 0.07% in potassium content and 0.04% in phosphorus content. The mixture of the food waste with dry leaf had the nutrient of 0.061% in nitrogen content, 0.09% in potassium content and 0.08% in phosphorus content. The mixture of the food waste with cow manure compost had nutrient content of 0.063% in nitrogen content, 0.1% in potassium content and 0.08% in phosphorus content. The addition of dry leaf in food waste mixture has significantly improved potassium content by 27.4% and phosphorus content by 86%, while for the addition of cow manure in food waste mixture has significantly improved potassium content by 41.1% and phosphorus content by 100%. Using dry leaf and cow manure in Cowtech anaerobic digestion is recommend in improving nutrient content of food waste compost. Profiling pattern in pilot scale anaerobic digester was determined by feeding of pure food waste and mixture of the food waste with cow manure in a steady-state inputoutput manner. The retention time of anaerobic food waste digestion of 30 days for complete digestion was observed based on measured physic-chemical properties of total carbon content, total nitrogen content and total volatile solid. The 30 days anaerobic digestion period take place efficiently is more than sufficient for a complete anaerobic digestion process.